2016
DOI: 10.7324/japs.2016.600114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro antimicrobial activity of extracts from Cassia obtusifolia L. and Senna sophera (L.) Roxb against pathogenic organisms

Abstract: Cassia species have been of medicinal interest due to their good therapeutic value in folk medicine. In the present study petroleum ether, ethanol and chloroform extracts from leaf and stems of Cassia obtusifolia and Senna sophera were investigated for their antimicrobial activities against some pathogenic microbes in vitro. The C. Obtusifolia leaf extracts in pet ether and chloroform showed more sensitivity against E. faecalis (MIC 0.2725mg/ml and MIC 0.2647) and ethanol extracts against A. fumigatus (MIC 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The presence of the nanomaterial at a certain concentration in the miswak extract as an antibiotic improves strength of miswak extract as an antibiotic. 20,22…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the nanomaterial at a certain concentration in the miswak extract as an antibiotic improves strength of miswak extract as an antibiotic. 20,22…”
Section: Resultsmentioning
confidence: 99%
“…According to the Clinical and Laboratory Standards Institute (CLSI) standards, all isolates' antimicrobial hindrance plans were analyzed using the reference stock microdilution system. 21,22 PCR upgrade of the mecA quality recognized methicillin impediment in S. aureus and S. epidermidis strains. 23 The revised Hodge test 21 was used to confirm carbapenem resistance in gram-negative bacteria.…”
Section: Bacterial Clinical Isolatesmentioning
confidence: 99%
“…faecalis (MIC 0.3009 mg/mL), and chloroform extracts showed sensitivity against E . faecalis MIC 0.4946 mg/mL [ 18 ]. The whole plant extract of C .…”
Section: Bioactivitymentioning
confidence: 99%
“…According to Rahman et al 2017, flower part of the plant showed good antibacterial activity against B. cereus. Deshpande and Naik, (2016) found that leaf and stem extracts of C. obtusifolia in pet ether showed more activity against E. faecalis. The leaf extract of S. sophera in pet ether showed more sensitivity against C. albicans, ethanol extracts against E. faecalis and choloroform extracts against C. albicans.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the occurrence of various phytoconstituents, the plant is suitable for treating a variety of ailments and has the potential to provide valuable drugs for human use (Tripathi and Kohli, 2012). Traditional wounds or burns, which may occur due to bacteria or fungi, are treatable by the leaf extract of Cassia sophera (Deshpande and Naik, 2016). Although some antimicrobial analyses were carried out different parts of the plant but no systemic researches were done for leaf, flower, seed and stem parts of the plant.…”
Section: Introductionmentioning
confidence: 99%